2004
DOI: 10.1007/s10549-004-0783-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary glutamine on tumor glutathione levels and apoptosis-related proteins in DMBA-induced breast cancer of rats

Abstract: Glutamine (GLN) is a non-essential amino acid that is present in nearly every biochemical pathway and is the major intraorgan nitrogen carrier. GLN via glutamate, is one of the precursors for the synthesis of glutathione (GSH), the major endogenous antioxidant in mammalian cells, which protects them from oxidative injury and cell death. Cancer cells have higher GSH levels than the surrounding normal cells, which attributes to a higher rate of cell proliferation and resistance to chemotherapy. Therefore, select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 48 publications
3
38
1
1
Order By: Relevance
“…During 1 h of acute phase of seizures, no case of fatality was observed between the adult rats. However, during the 24 h observation of this phase, 63% of adult animals died (Cavalheiro et al, 1994;Todorova et al, 2004). Similarly, these results for the behavioral alterations in pilocarpine model were described previously by Marinho et al (1998).…”
Section: Behavioral Alterations In Epilepsy Modelsupporting
confidence: 88%
“…During 1 h of acute phase of seizures, no case of fatality was observed between the adult rats. However, during the 24 h observation of this phase, 63% of adult animals died (Cavalheiro et al, 1994;Todorova et al, 2004). Similarly, these results for the behavioral alterations in pilocarpine model were described previously by Marinho et al (1998).…”
Section: Behavioral Alterations In Epilepsy Modelsupporting
confidence: 88%
“…The most important H 2 O 2 scavenging enzymes and concerned proteins having antioxidant capacity comprise CAT, GPx, GR enzymes associated with the synthesis of reduced GSH (Halliwell & Gutteridge, 1996) and a group of cysteine containing proteins known as thioredoxins, thioredoxin peroxidases (peroxiredoxins), and glutaredoxins (Kumar & Holmgren, 1999;Rhee, et al, 1999;Powis, et al, 2000;Holmgren, 2000). When ROS production is enhanced, the antioxidant scavenging capacity is disturbed and this results in the development of oxidative stress which leads to tissue injury and apoptosis activation (Todorova, et al, 2004).…”
Section: Antioxidant Defence Systemsmentioning
confidence: 99%
“…In breast cancers of rats, it was suggested that dietary glutamine supplementation decreased tumor GSH levels and suppressed cells by activation of apoptosis in tumor cells (Todorova et al 2004). Studies on Ehrlich ascites tumors (Carretero et al 2000) and melanomas (Benlloch et al 2006) demonstrated that a glutamine enriched diet increases glutaminase activity, promotes accumulation of cytosolic glutamate and inhibits GSH transport into mitochondria.…”
Section: Discussionmentioning
confidence: 99%